A Versatile and Cost Effective Multimodal Wheelchair - Sampath Dakshina Murthy, A; Rudra Pratap Das, Dr; S.Koteswara Rao, Dr (International Journal of Engineering and Technology, 2018)
The aim of this endeavor is to design a wheelchair to suit to the needs of such persons .By incorporating temperature and humidity sensor, IR sensor, FSR sensor and voice recognition sensor/module ,the device is quiteÂ versatile in attending to the basic problems encountered .After testing ,it was found that this apparatus helps in avoiding obstacles. If allows the person to use his tongue of required. The additional benefit is to have voice recognition for movement .Cost effectiveness is yet another merit of the proposed system.Â Â Â